Flow of a viscous fluid over an infinite rotating and porous disk with stretching (shrinking) effects - Bilal, Muhammad; Khan Marwat, Dil Nawaz; Ali, Aamir (Revista Mexicana de Física, 2020)
A viscous flow is maintained over a porous and rotating disk. The porous disk is stretched (shrunk) with the non-uniform velocity in the radial direction. Note that the viscous fluid is injected (blown) normally with non-uniform velocity. The study is under taken by considering the combined and individual effects of injection (suction), stretching (shrinking) and rotation. The kinematics properties associated with the disk are depending upon the radial coordinate. The governing partial differential equations (PDE’s) are simplified and transformed into a new system of DE’s. The set of boundary value ODE’s is solved with the help of a numerical method. The transformed equations (presented over here) are new and to the best of authors knowledge, the equations are not published in literature. In particular cases, the modeled equations may reduce to the classical problems of rotating disk flows. The previous models of rotating disk flows with or without porosity and stretching (shrinking) effects are summarized into a single model. For fixed value of the governing parameters and different sizes of "infinity", no increase/decrease in the thickness of boundary layer is seen but the profiles of velocity components and pressure are significantly changed with the different levels of "infinity".